Sustainability analysis and development strategy of crystal guava tourism: An evidence from Bojonegoro Regency, Indonesia - Hartono, Rio Cahyo; Efani, Anthon; Susilo, Susilo (Publisher of Widyagama University of Malang (UWG Press), 2024)
Tourism in Indonesia holds immense potential for bolstering national income and fostering economic growth. Agrotourism, an emerging sector, intertwines tourism activities with agriculture, exemplified by the guava crystal orchads in Padang Village, Bojonegoro Regency. Despite its promise, the full potential of this agrotourism destination remains untapped. A mixed-method approach was employed in a study to assess its sustainability comprehensively. Quantitative data was initially collected and analyzed using multidimensional scaling (MDS), followed by SWOT analysis. Findings indicate that while the ecological dimension demonstrates strong sustainability, other aspects such as the economy exhibit room for improvement. Consequently, various sustainability formulation strategies are proposed. The S-O strategy advocates collaboration with external stakeholders under favorable terms, while the W-O strategy emphasizes heightened promotional efforts and collaborative ventures to enhance human resource quality. Moreover, the S-T strategy entails intensifying promotional activities to counter competitors, whereas the W-T strategy focuses on enhancing accessibility, diversifying product offerings, and fostering collaborations to tackle challenges effectively. Implementation of these strategies is anticipated to furnish managers and policymakers with a pragmatic framework to enhance the sustainability. In essence, stakeholders can propel the crystal guava orchard agrotourism towards greater sustainability, thereby contributing significantly to the economic advancement of the region.JEL ClassificationÂ A14; Q26; Z30To cite this article: Hartono, R. C., Efani, A., & Susilo. (2024). Sustainability analysis and development strategy of crystal guava tourism: An evidence from Bojonegoro Regency, Indonesia. Journal of Socioeconomics and Development, 7(1), 77-88. https://doi.org/10.31328/jsed.v7i1.5440